2003
DOI: 10.1210/en.2003-0098
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Induces Apoptosis of Anaplastic Thyroid Cancer Cells via Inhibition of Protein Geranylgeranylation and de Novo Protein Synthesis

Abstract: Lovastatin has been used to treat hypercholesterolemia through blocking the mevalonate biosynthesis pathway. Inhibition of mevalonate synthesis may result in antiproliferation and cell apoptosis. The aim of the present study was to examine the apoptotic effect of lovastatin in human ARO cells and delineate its underlying molecular mechanism. Our results showed that lovastatin dose- and time-dependently induced apoptosis in ARO cells. Pretreatment with cycloheximide dose-dependently suppressed lovastatin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 34 publications
6
74
1
Order By: Relevance
“…As isopentenyl PPi is also depleted by statin exposure, it would be unavailable to the statin-treated cell (49,50). These results, as well as the ability of GGTI-298 to induce apoptosis comparably with statins in sensitive tumor lines, build on previous reports (1,11,16,41) to clearly indicate the importance of protein geranylgeranylation in statininduced apoptosis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As isopentenyl PPi is also depleted by statin exposure, it would be unavailable to the statin-treated cell (49,50). These results, as well as the ability of GGTI-298 to induce apoptosis comparably with statins in sensitive tumor lines, build on previous reports (1,11,16,41) to clearly indicate the importance of protein geranylgeranylation in statininduced apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…We and others have shown that of these downstream end-products, GGPP most consistently reverses statin-induced apoptosis in sensitive tumor cells (1,11,16,41). To evaluate the mechanism of lovastatininduced apoptosis in MM, four sensitive MM cell lines (KMS11, OPM2, H929 and OCI MY7) were screened by 3-4,5-dimethylthiazolyl-2,2,5-diphenyl tetrazolium bromide assay, as we have previously conducted (41).…”
Section: Mevalonate and Ggpp Abrogate Lovastatin-induced Apoptosis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in concordance with the observation in thyroid cancer that Rho protein is the pivotal element for cellular survival, whereas farnesylation of Ras proteins was not involved. 30,31 Interestingly, the isoprenylated proteins did not influence the cytomorphology of the cells, 30 because RhoA has been implicated in changes of cell morphology, formation of stress fibers, and focal adhesion. 48,49 The roles of Rho protein and Rho kinase in multiple myeloma are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Rho/ROCK activation also plays a pro-survival role during oxidative stress (H 2 O 2 )-induced intestinal epithelial cell injury via activation of PKCδ and PKD [129]. In anaplastic thyroid cancer cells, inhibition of Rho by lovastatin or inhibition of ROCK by Y27632 induces cytochrome c release, activation of caspases 3 and 9, and apoptosis which required de novo protein synthesis [154]. Inhibition of Rho or ROCK results in activation of caspases 3, 8 and 9, and glioma cell apoptosis [110].…”
Section: In Vitro Evidencementioning
confidence: 99%